A Study On Conceptual Design of a Drone for Transportation in The Agricultural Sector - M. Nor, Muhammad Faris; Hassan, Mohd Fahrul (Journal of Sustainable Manufacturing in Transportation, 2022)
A drone is a fast-growing technology that has been used in many applications in the world. The drone also is a new solution for the transportation process in the agricultural sector. The primary purpose of this project is to explore the potential of drone or Unmanned Aerial Vehicle (UAV) to reduce the dependence on fossil-fueled vehicles to transport the crops within the farm and from the farm to the seller. The use of drones will create lower emission of carbon dioxide and toxic gases that are usually generated by fossil-fueled vehicles. Besides, this research is also essential to reduce the health issues that currently appear from agriculture activities. The objective of this project is to determine the parameters to design a suitable drone for transportation in the agricultural sector. In addition, the design of the drone must be able to carry a maximum of 10 kg of payload, which can be analyzed by simulation and analysis. The simulation and analysis are performed by SolidWorks software. The conceptual design of the drone is proposed by following the George E. Dieter model of the design process. In addition, a simulation on the strength of the drone components and analysis on the thrust of the motor have been conducted to verify the proposed drone design concept based on the determined parameters. The cost estimation of the drone is about RM17683.65 and the overall weight is 26.823 kg. In conclusion, the drone design concept for transportation in the agricultural sector is proposed as a preliminary study for future works.